2004
DOI: 10.3171/spi.2004.100.1.0046
|View full text |Cite
|
Sign up to set email alerts
|

Rotational and transpositional flaps for the treatment of spinal wound dehiscence and infections in patient populations with degenerative and oncological disease

Abstract: Object. Wound-related complications following complex posterior spine procedures may result in the need for serial debridements and may place the instrumentation at risk. Numerous treatments have been advocated for this problem, but each has limitations. In this article the authors discuss the experience from two large teaching institutions at which rotational and transpositional flaps were used in the management of deep wound infections and dehiscen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 38 publications
0
36
0
2
Order By: Relevance
“…Because of their immunocompromised [17,30,33,34]. For these patients with limited life expectancies, the appropriate treatment is to achieve relief of pain and to regain function, thus improving the quality of the life as quickly as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Because of their immunocompromised [17,30,33,34]. For these patients with limited life expectancies, the appropriate treatment is to achieve relief of pain and to regain function, thus improving the quality of the life as quickly as possible.…”
Section: Discussionmentioning
confidence: 99%
“…The flap coverage is the standard treatment of infected wounds after spine surgery [9,14,15,27,32,41,45,46,63,66]. The use of omental transposition in the treatment of recurrent sarcoma of the back was also described [38].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some authors showed that instrumentation salvage is possible when techniques such as serial debridements, antibiotic medication, irrigation-suction systems and delayed primary closure of the wound are used [39,42,51,54,59,60,65]. Primary or delayed primary closure is often not possible and muscle flaps are required to close the dead space and to provide soft tissue coverage [15,27,46,63]. The muscle flaps, however, as extensive surgical procedures bear a significant morbidity for these critically ill patients [61,69].…”
Section: Introductionmentioning
confidence: 99%
“…The dose tolerance for organs at risk could be better contoured. Vitaz et al reported that prior adjuvant treatment modalities such as chemotherapy or EBRT typically increase perioperative morbidity and mortality following spinal surgery [18]. The best surgical outcomes are achieved with radical resection of the tumor (removal of the whole spine) [19].…”
Section: Discussionmentioning
confidence: 99%